Kedudukan Hak Cipta Sebagai Jaminan Hutang Pada Perjanjian Kredit Bank - Prayogi, Muhammad Rizki; Haliwela, Nancy Silvana; Pariela, Marselo Valentino Geovani (Faculty of Law Universitas Pattimura, 2024)
ABSTRACT: Regulation of the Government Number 24 Year 2022 on Creative Economy, Article 7 in this regulation states that in the implementation of intellectual property-based financing schemes, financial institutions, whether banks or non-bank financial institutions, are allowed to use intellectual property as collateral for loans. In its implementation, there are still various challenges and obstacles faced, including the difficulty of determining the value of copyright, the lack of clear concepts related to feasibility, and the absence of execution rules from the Bank Indonesia (BI), Financial Services Authority (OJK), and Banking related to intellectual property assets as loan collateral. The method of research used is legal normative, which examines legal materials such as legislation, legal theory, and scholars' opinions to solve the problem being studied. The purpose is to find out and explain the position of copyright as collateral in bank credit agreements and the legal strength of copyright as collateral in bank credit agreements. The results of this research indicate that the position of copyright as collateral in bank credit agreements has been regulated in the Copyright Law and the Government Regulation on Creative Economy. However, its implementation is still hindered due to the lack of policies from Bank Indonesia (BI) and the Financial Services Authority (OJK).